Pomacea canaliculata (Mollusca, Gastropoda) in Patagonia: potential role of climatic change in its dispersion and settlement - Darrigran, Gustavo (2011)
Pomacea canaliculata (Lamarck, 1822) (Mollusca Gastropoda) shows a large native distribution range in South America, reaching as far south as 37o S (Buenos Aires, Argentina). This species was deliberately introduced into Southeast Asia around 1980 and subsequently underwent a rapid intentional or accidental dispersal into many countries in the region. It was also introduced into North and Central America and Hawaii. In this contribution we record the presence of P. canaliculata in Patagonia, assessing the possible influence of climatic change in the new establishment of this species there. Three samplings (between September 2004 and April 2005) were carried out at 38o 58' 20.2" S-68o 11' 27.3" W. In the sampling we found two adult specimens of P. canaliculata and numerous egg clutches. Pomacea canaliculata is naturally distributed in the Plata and Amazon Basins. The southern boundary of this species has been established as the isotherms of 14 oC and 16 oC in Buenos Aires province, and precipitations of 900 to 600 mm/year. This study also analysed variations in annual temperature and precipitation in Patagonia. Average temperatures show an increase over the years, although not constantly. Important modifications in precipitation regime in northern Patagonia, triggered by global climatic changes, could be beneficial for the settlement of populations of P. canaliculata in this new area, where precipitation increased enough to reach values similar to those in the southernmost area of distribution of this species.